Impression membrane for the diagnosis of microbial keratitis. Issue 5 (16th September 2015) - Kaye, Stephen; Sueke, Henri; Romano, Vito; Chen, Jern Yee; Carnt, Nicole; Tuft, Stephen; Neal, Timothy
Abstract : Purpose: To evaluate a corneal impression membrane (CIM) for isolation of bacteria, fungi and acanthamoeba in suspected microbial keratitis. Methods: Consecutive patients presenting with suspected microbial keratitis were included. For each patient, samples were collected in a random order using a surgical blade and a 4-mm-diameter polytetrafluoroethylene CIM disc, and transported in brain heart infusion broth. Risk factors, best corrected visual acuity (BCVA), size, location, depth and healing time of the ulcer were recorded. The microbial isolation rate was used to compare sampling methods. Results: 130 patients were included (mean age 62.6 years, SD 19.0). An antimicrobial had been used prior to presentation in 36 (27.7%) patients. Mean major and minor ulcer diameters were 2.1 mm (SD 2.0) and 1.6 mm (SD 1.7). Mean healing time was 12.4 days (SD 13.6). BCVA at presentation and following healing was 0.7 (SD 0.7) and 0.62 (SD 0.7) (p=0.34). There were 66 isolates (50.8%); 53 (40.8%) using a CIM and 35 (26.9%) using a blade (p=0.02). Staphylococcus aureus and coagulase-negative staphylococci were the commonest isolates. Isolation rate was not influenced by organism type, although in four cases Acanthamoeba spp. were isolated; three using CIM and one a blade. Conclusions: In this study, the isolation of microorganisms from cases of suspected microbial keratitis was significantly higher using a CIM than a surgical blade. A CIM may be a useful alternative or addition for sample collection in microbial keratitis.